2010
DOI: 10.1075/eww.31.1.03ric
|View full text |Cite
|
Sign up to set email alerts
|

Preterite be

Abstract: In this paper I analyse variation in the use of past tense be in data from Morley, a suburb of Leeds, in the North of England, using both real-time and apparenttime data. Rather than concentrating on the traditional aspects of this variable, namely alternation between was and were, I identify four phonetic variants of the past tense be system. I propose that the community under consideration are adopting intermediate variants that, both in terms of perception and production, lie between the standard (British) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Saunders (1999) focuses on how Americans influenced scholars in Western Europe through conference subsidies and publications. Major conferences in the 1950s and 1960s strengthened Anglo–American collaboration in teaching English with key contributors of the time urging that teaching English as a foreign language is apolitical but can make the world a better place (Richards, 1968). Moreover, Cecil Rhodes who held the superiority of the Anglo race set up the Rhodes scholarship to fund scholars who would spread British influence when they left Oxford University.…”
Section: English Language In the Context Of Globalizationmentioning
confidence: 99%
“…Saunders (1999) focuses on how Americans influenced scholars in Western Europe through conference subsidies and publications. Major conferences in the 1950s and 1960s strengthened Anglo–American collaboration in teaching English with key contributors of the time urging that teaching English as a foreign language is apolitical but can make the world a better place (Richards, 1968). Moreover, Cecil Rhodes who held the superiority of the Anglo race set up the Rhodes scholarship to fund scholars who would spread British influence when they left Oxford University.…”
Section: English Language In the Context Of Globalizationmentioning
confidence: 99%
“…It has been found that ethnic social contexts greatly influenced was/ were variation for young speakers in London (Cheshire & Fox, 2009). Richards (2010) investigated a variety in Leeds, England, to find that four intermediate variants of was/were are being reallocated according to polarity. Recently, Moore (2011) used past be analysis to examine how factors such as socioeconomic status constrain the agency of practice-based social groups, and Tagliamonte and Baayen (2012) used was/were variation to illustrate the utility of mixed-effects models and conditional inference trees.…”
Section: P R E V I O U S R E S E a R C H O N W A S P A R A D I G M L mentioning
confidence: 99%
“…Like new variants of past be in stigmatized spectrums for other vernacular communities (Hazen, 1998;Richards, 2010), contracted was appears to be socially unconditioned not only because of its reduced form, but also its similarity to existential, present tense there's.…”
Section: U N a S S U M I N G Y E T I N F L U E N T I A L : C O N T R mentioning
confidence: 99%
“…Indeed, in terms of morphosyntactic features studied through a variationist perspective in English, it is among those which has received the most attention (in addition to research cited above, see e.g. Feagin , Eisikovits ; Smith ; Schreier ; Pietsch ; Adger and Smith ; Cheshire and Fox ; Tagliamonte ; Moore ; Richards ). The widespread divergence of the past tense paradigm in English dialects from the prescribed norms of standardized English has led Chambers (: 128) to posit was generalization (default singular as he calls it) as one of the vernacular universals of English.…”
Section: Introductionmentioning
confidence: 99%